Сравнительный анализ сочленовных поверхностей суставных отростков пояснично-крестцовых позвонков некоторых млекопитающих - Пылыпчук, О.Я. (Вестник зоологии, 1976)
The area of articular facets of lumbosacral region articular processes was determined for 30 animals. The dimensions were compared in each articulation for representatives of plantigrades, digitigrades and unguligrades. It is established that the dimensions and shape of the facets of the lumbosacral vertebrae articular processes ensures the strength and mobility of this spinal region, the maximum mobility region being different in different animals. Three types of joints may be distinguished in the lumbosacral region of the examined animals: (a) semimobile joints plane, congruent, with a facet reserve for movement; (b) hinge joints — trochoid, congruent; (c) most mobile joints — close to spheroid, with a reserve for movement.